Jarik Ma'siti Learning Management (Case Study at SMPN 10 Malang City) - Wasila, Nur Fatkhiya Warda; Sultoni, Sultoni; Juharyanto, Juharyanto (Journal of Education for Sustainability and Diversity, 2025)
Learning for children with special needs requires a structured approach and is tailored to the individual needs of each child. This research aims to describe learning patterns, learning mechanisms and learning strategies implemented through the Jarik Ma’Siti program for children with special needs at SMPN 10 Malang City. The method in this research uses a qualitative approach to case study design using interview, observation and documentation data collection techniques. The results of this research show (1) the learning mechanism used at SMPN 10 Malang City through Jarik Ma’Siti for children with special needs is differentiation by modifying the curriculum and teaching methods according to the needs of students; (2) the learning pattern used at SMPN 10 Malang City through Jarik Ma’Siti for children with special needs begins with careful learning planning, structured learning organization, implementation of differentiated learning, and continuous learning evaluation; and (3) the learning strategy used at SMPN 10 Malang City through Jarik Ma’Siti for children with special needs is to use supporting learning media and additional programs to improve students' personalities and life skills.